Penerapan Outcome-Based Education dalam Pengajaran Manajemen Pemasaran dan Studi Benchmarking: Penerapan Outcome Based Education dalam Pengajaran Manajemen Pemasaran dan Studi Benchmarking - Lena Magdalena; Sutrisna; Asher Nuche; Asri; Ariesya Aprillia; Sandy Setiawan (ADI Publisher, 2025)
In the era of globalization, higher education faces significant challenges in ensuring the quality and relevance of graduates at the international level. One strategy to enhance global competitiveness is through international benchmarking, a process of comparing institutional performance with global standards or leading institutions in the field. International benchmarking goes beyond academic outcomes it also includes curriculum development, teaching methods, and the improvement of student skills to meet global industry demands. Within the framework of Outcome-Based Education (OBE), the achievement of learning outcomes is a key indicator of a program’s success. OBE emphasizes the results students must attain after completing their studies, including technical skills, critical thinking abilities, and professional competencies. International benchmarking plays a crucial role in designing OBE-based curricula to ensure graduates possess internationally recognized competencies. However, its implementation poses several challenges, such as limited resources, institutional readiness to align with global standards, and difficulties in accessing valid and relevant comparative data. This study aims to explore the impact of international benchmarking on the achievement of learning outcomes within the OBE framework by examining case studies and analyzing data from institutions that have implemented benchmarking practices. The study employs case studies and data analysis from institutions that have implemented international benchmarking practices. The findings are expected to provide strategic insights into the effectiveness of benchmarking in enhancing higher education quality. Additionally, the study aims to identify adaptive and sustainable implementation strategies for educational institutions in Indonesia.